PENGARUH BOARD DIVERSITY TERHADAP KINERJA PERUSAHAAN DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERATING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2021) - Sheilla Nur Rahma; Wisnu Mawardi (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to examine the effect of Board diversity projected by gender diversity and age diversity on firm performance with institutional ownership as a moderating variable. The population in this study are manufacturing companies listed on the IDX for the 2017- 2021 period. The total population in this study were 195 manufacturing companies. The sampling technique used was purposive sampling and obtained a sample of 58 companies. The data analysis method used is moderated regression analysis with the SPSS version 22 application. The results of this study indicate that gender diversity has a positive effect on firm performance, age diversity has a negative and significant effect on firm performance, institutional ownership is not able to moderate the effect of gender diversity on firm performance, and institutional ownership able to increase the effect of age diversity on firm performance